ANALISIS CAR, NPF, FDR, NOM DAN SIZE TERHADAP RISIKO BISNIS : STUDI PADA BANK UMUM SYARIAH DI INDONESIA PERIODE TAHUN 2010-2014 - Hidayat, Eko Nur; Widyarti, Endang Tri (Diponegoro Journal of Management, 2016)
This study aims to examine the influence of Capital Adequacy Ratio (CAR), Non Performing Financing (NPF), Financing to Deposit Ratio (FDR), Net Operating Margin (NOM) and the size of the company (size) of the business risk (SDROA) Islamic commercial bank in Indonesia period 2010-2014.The sampling technique used in this research is purposive sampling with criteria that Islamic banks publish annual financial reports and monthly basis during 2010-2014. The data used in this study was obtained from the annual financial statements and monthly on the official website of Bank Indonesia, the official website of Otoritas Jasa Keuangan and the official website of each Islamic commercial bank that the research sample. Samples are 11 sharia banks in Indonesia. Methods of data analysis in this study with multiple regression analysis, then use the test classic assumptions and hypothesis testing using the F statistic, statistical test t and test the coefficient of determination Adjusted R2 with a significance level of 5%.The results showed that the independent variables simultaneously (F test) affect the SDROA with a significance level of 0.006. While partially (t test) showed that the CAR and FDR variable positive and significant impact on SDROA. Variable NPF and NOM positive and not significant to SDROA. Meanwhile, the variable size and no significant negative effect on SDROA. Adjusted R2 value of 0.21, which means that the ability of the five independent variables can explain SDROA by 21%, while the remaining 79% is explained by other factors not included in the research model.